Effect of Carbonic Anhydrase Inhibitor Combination on Fertility Male Rats - Anmar Shukr Mahmood (Journal of Global Pharma Technology, 2016)
Carbonic anhydrase inhibitors are many drugs, the main usage in epilepsy and raised intracranial pressure and the most commonly used are acetazolamide and topiramate. Twenty healthy adult males Wistar rats After acclimatization three weeks and divided to two groups randomly (10 rats/group) and treatment for 60 days as follows: high dose (Hd) group administrated 30 mg/kg/B.W of Acetazolamide and 9mg/kg/B.W of Topiramate and low dose (Ld) group received 5mg/kg B.W of Topiramate and 30 mg/kg B.W of Acetazolamide orally/day. Serum Hormones concentration tested are testosterone (ng/ml) and follicular stimulation hormones (FSH), Serum luteal hormones (LH) mlU/ml. The histological section showed the pathological changes in the Hd group while in the Ld have semi normal changes, the results confirm that the rats received of low dose more safety than the high dose of these drugs combination.